X-ray Fluorescence Spectroscopy of Picrolite Raw Material on Cyprus - Moutsiou, Theodora; Ioannides, Demetrios; Charalambous, Andreas; Schöder, Sebastian; Webb, Sam M.; Thoury, Mathieu; Kassianidou, Vasiliki; Zomeni, Zomenia; Reepmeyer, Christian (My University, 2022)
Picrolite artefacts comprise some of the most distinctive material remains in the prehistory of the island of Cyprus, in the Eastern Mediterranean. Picrolite exploitation dates from at least 12,000 years ago for the manufacture of personal ornaments and items with a symbolic function. It is commonly assumed that picrolite nodules were collected in secondary deposits on an ad hoc basis. This narrative, however, ignores the fact that picrolite carriers can only be found in very specific locations on the island, discrete from each other. Here we report initial outcomes of the application of handheld portable X-ray fluorescence (HHpXRF) and synchrotron-based X-ray fluorescence spectroscopy (SR-µXRF) to the analysis of picrolite raw materials performed at the newly opened PUMA beamline of the SOLEIL Synchrotron Radiation Facility. Our work refines the basic characteristics of the elemental constituents of the picrolite raw material and highlights key micro-structural differences between two distinct source regions on the Troodos Massif in western Cyprus. Picrolite source characterisation is expected to contribute significant new knowledge to the study of rare raw material consumption, prehistoric social organisation, networking and possible long-distance exchange of this idiosyncratic raw material within and beyond the island’s geographic boundaries.
Keywords: Cyprus; picrolite; sourcing; synchrotron microspectroscopy; X-ray fluorescence